A high-throughput bioanalytical assay to support pharmacokinetic interaction study of oxycodone and diazepam in Sprague Dawley rats. Issue 2 (3rd January 2020) - Pilli, Nageswara R.; Narayanasamy, Suresh; Xu, Lin; Chockalingam, Ashok; Shea, Katherine I.; Stewart, Sharron; Rouse, Rodney; Patel, Vikram; Matta, Murali K.
Abstract : A high-throughput bioanalytical method for the simulataneous determination of oxycodone and diazepam to support the evaluation of respiratory depression in rats upon co-administration of oxycodone and diazepam. Abstract : Benzodiazepines potentiate respiratory depression when combined with an opioid leading the U.S Food and Drug Administration (FDA) to recommend updating the labels of these products with a boxed warning for respiratory depression with co-use. Potential respiratory depression upon co-administration of opioids with some psychotropic drugs is not well understood. The FDA is currently investigating various psychotropic drug interactions with the commonly used opioid, oxycodone, in a rat model assessing respiratory depression. Pharmacokinetic and/or pharmacodynamic (PK/PD) interaction between oxycodone and diazepam was evaluated in a positive control arm of these experiments. Understanding the systemic exposure of these drugs alone and in combination exposures was used to identify PK/PD interactions. The authors developed a simple, high throughput liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay for the simultaneous determination of oxycodone and diazepam in rat plasma. Sample preparation was performed in 96-well protein precipitation plates using acetonitrile. Processed samples were analyzed using a C18 column with a gradient mobile phase composed of 2 mM aqueous ammonium formate with 0.1% formic acid and acetonitrile. A Thermo TSQ Quantum Ultra AM triple quadrupole mass spectrometer with multiple reaction monitoring (MRM) mode was used to acquire data. The method was validated for selectivity, specificity, linearity, precision and accuracy, dilution integrity and stability. The validated LC-MS/MS assay was utilized for quantifying oxycodone and diazepam in concomitantly treated Sprague Dawley (SD) rats.